1990
DOI: 10.1200/jco.1990.8.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic, computed cranial tomographic, and magnetic resonance imaging abnormalities in patients with small-cell lung cancer: further follow-up of 6- to 13-year survivors.

Abstract: To determine the subsequent evolution of neurologic, neuropsychologic, and intracranial anatomic findings in long-term survivors of small-cell cancer, we repeated an evaluation done 4 years previously in patients 6 to 13 years after treatment. Fifteen patients were reevaluated with a history and physical examination, mental status examination, neuropsychologic testing, computed cranial tomographic (CCT) scans, and magnetic resonance imaging (MRI). All but one was ambulatory and none were institutionalized. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…Crossen et al [18] conducted a wide-ranging review of neurological and neurocognitive adverse effects noted in patients after cranial irradiation in various settings: brain necrosis, seizures, or dementia reported sometimes after high-dose irradiation for primary gliomas, learning deficits in children receiving moderate dose cranial irradiation as treatment for ALL, an interaction between chemotherapy and radiation, and abnormalities in psychometric testing showing up more readily than positive findings on clinical examination. Johnson and coworkers studied long-term survivors of SCLC [19,20] finding a decline in neurocognitive function with some correlation with abnormalities on CT scan. Problems were more frequent when chemotherapy was given at the time of cranial Yang, Matthews 295 irradiation, or large radiation fraction size was employed.…”
Section: Neurocognitive Dysfunctions-nature and Causative Factorsmentioning
confidence: 99%
“…Crossen et al [18] conducted a wide-ranging review of neurological and neurocognitive adverse effects noted in patients after cranial irradiation in various settings: brain necrosis, seizures, or dementia reported sometimes after high-dose irradiation for primary gliomas, learning deficits in children receiving moderate dose cranial irradiation as treatment for ALL, an interaction between chemotherapy and radiation, and abnormalities in psychometric testing showing up more readily than positive findings on clinical examination. Johnson and coworkers studied long-term survivors of SCLC [19,20] finding a decline in neurocognitive function with some correlation with abnormalities on CT scan. Problems were more frequent when chemotherapy was given at the time of cranial Yang, Matthews 295 irradiation, or large radiation fraction size was employed.…”
Section: Neurocognitive Dysfunctions-nature and Causative Factorsmentioning
confidence: 99%
“…Surgical patients lost to follow-up with unknown chemotherapy receipt 7 or patients who refused chemotherapy 6 were excluded. All remaining 264 patients received systemic therapy as part of their initial therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Brain irradiation has been associated with gradual damage to white matter, as observed on imaging. 7,13 Preclinical studies suggest an association among late neurotoxicity, inflammation, and damage to neural progenitor cells in the hippocampus and subventricular zone. [14][15][16] A dose-volume histogram analysis of 2 prospective clinical trials demonstrated that radiation-induced neurotoxicity is predicted by radiation dose to specific regions of the brain, including the hippocampus, rather than dose to the whole brain.…”
Section: Advances In Radiation Oncology: October-december 2017mentioning
confidence: 99%
“…Such cognitive changes can occur both pediatric and adult patients and include progressive deficits in shortterm memory, spatial relations, visual motor processing, quantitative skills, and attention [2]. Neurocognitive dysfunction was reported to stabilize spontaneously or to progress over time [5,6]. In some cases, subcortical dementia might result which often is associated with gait disturbance and incontinence.…”
Section: Introductionmentioning
confidence: 99%